Thinking visually - Wigan, Mark.; ebrary, Inc. (Lausanne, Switzerland : AVA Academia, 2006)
Features the work of more than one hundred international illustrators, educators and students demonstrating diverse visual languages, contexts, ideas, techniques and skills. This title explores the importance of ideas, research, drawing and experimentation and is an educational tool featuring short exercises, methods, workshops, and techniques.
Includes bibliographical references.
Keywords: Graphic arts; Visual communication; Art -- Graphic Arts